2013
DOI: 10.1027/0227-5910/a000170
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Attitudes Among Medical Students in the United Arab Emirates

Abstract: The prevalence of suicidal ideation and attempts among medical students in the UAE was in the lower range in international comparison. Negative attitudes toward suicide were accompanied by a strong support for a suicidal friend, and both were related to religiosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
5
36
0
Order By: Relevance
“…Despite the relatively weak relationships found in this study, loneliness should be avoided and treated carefully because suicide causes a serious loss of not only individuals but also the national health workforce. The results showing the occurrence of suicidal ideation throughout life or in the previous year (37.7%-33.4%) were higher than found most previous medical and dental studies [9][10][11][12]14,16,17,[20][21] with the exception of the high prevalence in Taiwan (43.6%) 13 and Pakistan (35.4%). 15 Moreover, the results of our study showed the highest prevalence of suicide attempts compared to all previous studies on medical and dental students.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Despite the relatively weak relationships found in this study, loneliness should be avoided and treated carefully because suicide causes a serious loss of not only individuals but also the national health workforce. The results showing the occurrence of suicidal ideation throughout life or in the previous year (37.7%-33.4%) were higher than found most previous medical and dental studies [9][10][11][12]14,16,17,[20][21] with the exception of the high prevalence in Taiwan (43.6%) 13 and Pakistan (35.4%). 15 Moreover, the results of our study showed the highest prevalence of suicide attempts compared to all previous studies on medical and dental students.…”
Section: Discussionmentioning
confidence: 53%
“…The second section measured loneliness on the Revised UCLA Loneliness Scale. 29 The UCLA contains 20 items that are answered on a Likert scale from 1 to 4; (1) means "I have never felt this way", (2) "I feel this way rarely", (3) means "I feel this way sometimes" and (4) means "I feel this Journal of International Medicine and Dentistry 2018; 5(1): [11][12][13][14][15][16][17][18][19] way often". This UCLA was measured by the questions sum score ranging from 20 to 80, taken in consideration that some questions have reversed score.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four cross-sectional studies (n = 21 002) in 15 countries reported on the prevalence of suicidal ideation (Table 2). 4,5,34,62,65,73,74,79,112,160,165,167,174,[185][186][187][188][189][190][191][192][193][194][195] Medical student training level, continent or region, country, diagnostic criteria or screening instrument cutoff, and total Newcastle-Ottawa scores for the studies appear in eTable 1 in the Supplement. Newcastle-Ottawa score components for all 195 individual studies appear in eTable 2 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%